Prevalence of Upper Extremity Musculoskeletal Problems among Male and Female Dental Students - A cross sectional study - Tamknat Ilyas, Rabia Jawa, Hunza Zulfiqar, Sania Maqbool, Hafiz Muhammad Uzair Asghar, Abdul Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: To estimate gender difference in prevalence of UE MSDs among dental students. Cumulative trauma disorders (CTD), repetitive strain injuries (RSIs), and overuse syndrome are all terms used to describe MSDs. Overuse movement patterns involving repetitive and intense movements at the joint, as well as other risk factors, enhance the likelihood of musculoskeletal diseases in dentistry students. Aim: To provide the importance of the proper ergonomics and proper posture to dental students. So that to avoid upper extremity musculoskeletal disorders among them Methods: Data was collected from dentistry students studying at the University of Lahore in a descriptive cross-sectional survey. The data was collected using a standard Nordic Questionnaire. The SNQ is divided into two sections, one of which includes descriptive statistics and the other of which has a series of questions with yes/no questions that indicate the areas of the body impacted by MSDs and the locations of feelings experienced from the positional uncomfortable graphic. Results: According to the results, the dentistry student’s encountered U.E joints problems more during their daily life predominantly in shoulder and wrist joints and the pain evaluation prove the results. Conclusion: Dentistry students have a higher prevalence of UE MSDs with shoulder and wrist most affected according to the findings. Keywords: Musculoskeletal disorders, Standardized Nordic questionnaire, Dental students.